PERTIMBANGAN HAKIM DALAM MEMUTUSKAN BESARAN BUNGA MORATOIR: Analisis Putusan No: 04/Pdt.G/2011/PN Gto dan Putusan No: 13/Pdt.G/2020/PN Tar - Yori, Aurelius Kasimirus; Sutanto, Very Werson; Patricia, Rosa (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Based on the analysis conducted on two court decisions, namely Gorontalo District Court Decision No. 04/Pdt.G/2011/PN Gto and Tarakan District Court Decision No. 13/Pdt.G/2020/PN Tar, the results obtained illustrate the differences in the judges' perspectives in deciding moratorium interest due to default. In Decision No. 04/Pdt.G/2011/PN Gto, the judge decided that the moratorium interest to be paid by the defendant was 2 (two) percent per month, while in Decision No. 13/Pdt.G/2020/PN Tar, the judge decided that the moratorium interest to be paid by the defendant was 6 (six) percent per year or in accordance with the interest according to Article 1767 of the Civil Code. The judge in Decision No. 04/Pdt.G/2011/PN Gto adheres to the understanding of progressive law, daring to follow the development of society. In Decision No. 13/Pdt.G/2020/PN Tar tends to adhere to a rigid positivistic understanding while still implementing the provisions of the law